The Internal Job Market of the IMF's Economist Program. (IMF Working Papers; Working Paper ;, 2004)
This paper shows how the internal job market for participants in the IMF Economist Program (EPs) could be redesigned to eliminate most of the shortcomings of the current system. The new design is based on Gale and Shapley's (1962) Deferred Acceptance Algorithm (DAA) and generates an efficient and stable outcome. An Excel-based computer program, EPMatch, implements the algorithm and applies it to the internal job market for EPs. The program can be downloaded from http://www.people.hbs.edu/gbarron/EPMatch_ for_Excel.html.